Penerapan Model Problem Based Learning (PBL) pada Materi Program Linear untuk Meningkatkan Hasil Belajar Siswa - Bili, Maria Rosalia; Ate, Dekriati (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2018)
[Title: The Application of Problem Based Learning (PBL) Models to Linear Program Materials to Improve Student Learning Outcomes]. This research is a classroom action research that aims to improve the learning outcomes of linear programs through the application of the problem based learning model of class XII students of SMA N 1 Wewewa Utara in the odd semester of the academic year 2017/2018 with 36 students. Cycle I was held for 5 meetings and Cycle II was carried out for 4 meetings including the giving of the final test of Cycle I and Cycle II. Data retrieval is done using learning outcomes tests and observation sheets. The collected data were analyzed using quantitative and qualitative analysis. The results of this study indicate that (1) the value of classical completeness of learning outcomes of students of class XII IPA of SMA N. 1 Wewewa Utara at the end of the first cycle test was 61.11% with sufficient categories while the value of classical completeness of student learning outcomes in cycle II was 83.3% with a very good category and (2) The learning outcomes of students of class XII Natural Sciences at SMAN 1 North Wewewa in cycle I to Cycle II increased by 22.19% through the application of the problem based learning model.